Morphological variation of Solanum elaeagnifolium in south‐eastern Australia. (14th June 2013) - Zhu, X C; Wu, H W; Stanton, R; Burrows, G E; Lemerle, D; Raman, H
Summary: Solanum elaeagnifolium (silverleaf nightshade) is an invasive perennial weed in Australia, with aerial growth commencing in spring from either the perennial root system or the soil seedbank, with senescence occurring in autumn. A total of 642 S. elaeagnifolium individuals were collected at flowering from 92 locations in south‐eastern Australia to study morphological variation and its implications for management. Large morphological variation was found between individuals from different locations. Leaf length, width and area ranged from 1.44 to 10.6 cm, 0.39 to 4.09 cm and 0.41 to 25.8 cm 2 respectively. Plants from higher rainfall regions were significantly taller and had larger leaves, suggesting a possible correlation between rainfall and morphology. Scanning electron microscopy comparison of leaf surfaces showed lower trichome and stomatal densities on the adaxial surface (67.0 ± 3.3 trichomes mm −2 and 603.4 ± 29.2 stomata mm −2 respectively) than on the abaxial surface (131.9 ± 7.2 trichomes mm −2 and 813.7 ± 30.5 stomata mm −2 respectively). The morphological plasticity of S. elaeagnifolium highlighted in this study could probably contribute to its adaptability and partly explain its establishment and continuing expansion in Australia.